miR-206/133b Cluster: A Weapon against Lung Cancer? - Pan, Jing-Yu (Mol Ther Nucleic Acids, 2017)
Lung cancer is a deadly disease that ends numerous lives around the world. MicroRNAs (miRNAs) are a group of non-coding RNAs involved in a variety of biological processes, such as cell growth, organ development, and tumorigenesis. The miR-206/133b cluster is located on the human chromosome 6p12.2, which is essential for growth and rebuilding of skeletal muscle. The miR-206/133b cluster has been verified to be dysregulated and plays a crucial role in lung cancer. miR-206 and miR-133b participate in lung tumor cell apoptosis, proliferation, migration, invasion, angiogenesis, drug resistance, and cancer treatment. The mechanisms are sophisticated, involving various target genes and molecular pathways, such as MET, EGFR, and the STAT3/HIF-1α/VEGF signal pathway. Hence, in this review, we summarize the role and potential mechanisms of the miR-206/133b cluster in lung cancer.